Moya Moya’s disease in a 20-year-old female patient – case report - Hołowczuk, Magdalena; Orzeł, Anna Katarzyna; Janeczko, Dominika; Klatka, Barbara Zofia; Terpiłowski, Michał; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Introduction Moya-Moya disease is a rare disease of unknown etiology that causes pathological occlusion changes in the large intracranial arteries - the internal carotid artery and the proximal parts of the anterior and middle cerebral arteries. The disease occurs most often among young Asian women, and its most intensive development falls on the first decade of life. In most cases, Moya-Moya occurs in the form of transient ischemic attacks, strokes or cerebral hemorrhages. Case report A 20-year-old woman was admitted to the Neurosurgery Clinic for the surgical treatment of Moya-Moya disease. Patient with paroxysmal paresis of left and right limbs several times since 2016. In CT, MRI and angio-MRI, as well as DSA, critical narrowing of the internal carotid arteries, obstruction of the anterior and central lights of the cerebral arteries, with small vessels around the central arteries and their branches marked - bilaterally, but mainly on the right. The changes create an image resembling "clouds of smoke" that is characteristic of Moya-Moya’s disease. The patient was qualified for surgical treatment - revascularization of the cerebral cortex with the use of periosteal strips by multi-hole trepanation in the right fronto-temporo-parietal region. Periosteal stripes were introduced into the subarachnoid space to reproduce vessels of the cerebral cortex. Conclusion Because of the rarity of Moya Moya disease, it is very important to be alert vigilantly to avoid complications such as tetraparesis or mental retardation. Japanese surgery allows revascularization of the cerebral cortex without the need for an arterial bypass. The presented surgical method ensures good treatment effects and is preferred in young people due to the safety of the technique used. Keywords: Moya Moya disease, neurosurgery, hemorrhages